Static behavior of large stud shear connectors in steel-UHPC composite structures. (1st January 2019) - Wang, Jingquan; Qi, Jianan; Tong, Teng; Xu, Qizhi; Xiu, Hongliang
Highlights: This paper firstly investigated the push-out behavior of large stud shear connectors in UHPC. The application of large stud shear connectors in steel-UHPC composite structures could break through the limitation on the stud maximum diameter (25 mm). An empirical shear load-slip equation taking into account stud diameter was proposed. A new concept of concrete splitting wedge block was proposed to illustrate the mechanical mechanism and the shear strength enhancement of the studs in UHPC. Abstract: This paper presents an experimental study on the static behavior of large stud shear connectors embedded in ultra-high performance concrete (UHPC). Test parameters included stud diameter, stud aspect ratio, concrete strength, and concrete slab thickness. Headed studs of two sizes, 22 mm and 30 mm in diameter, were used in this study. Extensive splitting cracks on concrete slab were detected for the normal strength concrete specimen whereas no cracks were found for the UHPC specimen with 30 mm studs, indicating that UHPC matches well with large studs. The shear strength, shear stiffness and ductility of a stud with 30 mm diameter were approximately 15%, 45% and 60% higher than those of a stud with 22 mm diameter, respectively. Stud aspect ratio and concrete slab thickness showed no obvious influence on the static behavior of the test specimens and short stud shear connectors with an aspect ratio of 2.3 could develop full strength in UHPC slabs. An empirical equation taking into account stud diameter was proposed to predict the shear load-slip curve of headed studs. Lastly, the current stud shear strength design provisions were evaluated using the experimental data.